Rebuilding the Angolan body politic: global and local projections of identity and protest in O Herói/The Hero (Zézé Gamboa, 2004) - Sabine, Mark (Intellect Ltd, 2012)
This article uses a reading of Zézé Gamboa's award-winning 2004 feature as a basis for an exploration of post-conflict Angolan screen culture and of its impact both at home and internationally. It considers how O Herói’s depiction of a war-torn nation, and of the impediments to its reconstruction, negotiates between a socially-engaged film-making practice, informed by local tradition and the tenets of ‘Third Cinema’, and the demands of a globalised cinema market. The film achieves this compromise by deploying allegorical and symbolic tropes, familiar from the literature, cinema, and political discourse of the era of Angolan liberation (notably, the concept of a socialist ‘new man’), to complicate a superficially optimistic story of post-conflict rehabilitation, and to insinuate a critique of the authoritarian practices and neo-liberal policies of the MPLA government. Further to this, the article identifies strategies through which the film advertises the gulf between its fiction of individual triumph over adversity and, on the other hand, the grimmer reality of Angola’s post-conflict malaise. Finally, it considers how the film’s construction of an encrypted allegory also prompts the question of whether or not film production that depends upon the funding and agendas of international capital and neo-colonial powers can ever foster the resurgence of a genuinely ‘popular’ and progressive culture in post-conflict Angola.